Stimuli-responsive delivery vehicles based on mesoporous silica nanoparticles: recent advances and challenges. Issue 7 (16th January 2017) - Zhu, Jianhua; Niu, Yimin; Li, Yang; Gong, Yaxiang; Shi, Huihui; Huo, Qiang; Liu, Yang; Xu, Qunwei
Abstract : In the past decade, stimuli-responsive drug delivery vehicles based on surface-functionalized mesoporous silica nanoparticles have attracted intense interest as a new type of drug carrier. Abstract : In the past decade, stimuli-responsive drug delivery vehicles based on surface-functionalized mesoporous silica nanoparticles (MSNs) have attracted intense interest as a new type of drug carrier. These intelligent drug delivery systems have been demonstrated to enable precise drug release into highly specified targets and exhibit nearly "zero premature release" in systemic circulation. It is expected that an in-depth understanding of the basic mechanisms of the MSN-based stimuli-responsive drug delivery systems (DDSs) would further contribute to this breakthrough field of nanomedicine. In this review, the recent advances in the development of stimuli-responsive systems based on MSNs are summarized and discussed, including single stimuli-responsive DDSs, dual stimuli-responsive DDSs and multi stimuli-responsive DDSs. The challenges for stimuli-responsive DDSs based on MSNs with regards to future translation into clinical use are also simply discussed.